Role of quantitative intravoxel incoherent motion parameters in the preoperative diagnosis of nodal metastasis in patients with rectal carcinoma. Issue 4 (28th March 2016) - Qiu, Lin; Liu, Xiao‐Ling; Liu, Si‐Run; Weng, Ze‐Ping; Chen, Xiao‐Qiao; Feng, You‐Zhen; Cai, Xiang‐Ran; Guo, Chang‐Yu
Abstract : Purpose: To evaluate the diagnostic value of intravoxel incoherent motion imaging (IVIM) in differentiating metastatic and nonmetastatic lymph nodes in patients with rectal carcinoma. Materials and Methods: In all, 68 patients with histologically proven rectal carcinoma underwent an IVIM sequence (b = 0, 25, 50, 75, 100, 150, 200, 400, 600, 800, 1000, 1200, 1500, and 2000 s/mm 2 ) on a 3.0T MRI scanner. The IVIM parameters (D, D*, f, and apparent diffusion coefficient [ADC] values) in metastatic and nonmetastatic lymph nodes were measured and calculated. Receiver‐operating characteristic (ROC) analyses were conducted to determine the optimal thresholds, the sensitivities, and specificities for differentiation. Results: Mean D, f, and ADC values of metastatic lymph nodes were significantly greater than those of the normal lymph nodes ( P < 0.01), whereas the mean D* value of metastatic lymph node was statistically lower ( P = 0.03). The AUC, sensitivity, specificity, and the cutoff value, respectively, for differentiating metastatic from nonmetastatic lymph nodes for D, D*, f, and ADC were as follows: D, 0.9460, 89.25%, 91.04%, and 1.14 × 10 −3 mm 2 /s; D*, 0.6930, 64.18%, 82.80%, and 7.02 × 10 −3 mm 2 /s; f, 0.7810, 92.47%, 55.22%, and 0.27%; ADC, 0.8970, 87.10%, 88.06%, and 0.80 × 10 −3 mm 2 /s. The ROC curves demonstrated that the area under the ROC (AUC) of the D, ADC, f, and D* values successively decreased, and D had the highest AUC, with D* values being lowest. Conclusion: An IVIM sequence may be helpful in diagnosing metastatic lymph nodes of rectal carcinoma. Average D and ADC values are more sensitive than f and D* values in this differentiation. J. MAGN. RESON. IMAGING 2016;44:1031–1039.